Creative Economic Development Model Based on Coconut Products Through Business Mentoring - Millaningtyas, Restu; Hatneny, Aleria Irma (Journal of Entrepreneurship, Business and Economics, 2019)
Creative economy is an economic sector that has given contribution in creating jobs, increasing exports, creating innovation and creativity, and providing a positive social impact in improving quality of life and tolerance. This research take place in "Rizki Abadi" Small and Medium Enterprise (SME) in Sekardangan, Papungan Village, Kanigoro District, Blitar Regency. This SME produces coconut-based snacks called opak gambir. Several obstacles faced by this SME includes lack of innovation in product packaging, unstable raw material prices, inadequate human resources, and conventional marketing methods. The purpose of this research is to depict the model of Opak Gambir-based creative economy development through product innovation, problem identification, and solution making. This research uses primary and secondary data source which consist of direct field observations, interviews, journals, and other articles related. The result of this research found that simple packaging methods, inconsistent labeling and conventional marketing methods lead to inaccurate service and less extensive marketing reach. Unstable raw material price affects sales stability, while the quality of raw materials does not affect sales stability. The environment has no impact to the sales stability due to competition among SME's. Simple production equipment does not significantly affect the stability of sales, while the quantity of sealer affects production's punctuality. Skills and the amount of labor do not have an impact on sales stability. Meanwhile, business mentoring has an ability to help increase in sales due to its support in using online media for promotion and adding the quantity of sealer. In addition, it helps SME attain raw materials from Koperasi. Research paper Keywords: SME, Productivity, Creative economy, Opak gambir, Mentoring Reference to this paper should be made as follows: Millaningtyas, R., & Hatneny, A. I. (2018). Creative Economic Development Model Based on Coconut Products Through Business Mentoring, Journal of Entrepreneurship, Business and Economics , 6 (2), 115–131.